Dead Heat - Brennan, Allison (Thorndike, Maine : Center Point Large Print, 2015)
"Assigned to San Antonio's Violent Crimes unit, FBI agent Lucy Kincaid joins a task force called Operation Heatwave to apprehend known offenders with outstanding warrants. But when Lucy and her team try to bust two local brothers for jumping bail, she walks into a hotbed of pure evil"--
Keywords: United States -- Federal Bureau of Investigation -- Fiction -- Employees; Murder -- Fiction -- Investigation; Large type books; Suspense fiction